2021
DOI: 10.20892/j.issn.2095-3941.2021.0158
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic microenvironment induced spatial transcriptome changes in pancreatic cancer

Abstract: Objective: Hypoxia is a significant feature of solid tumors, including pancreatic ductal adenocarcinoma (PDAC). It is associated with tumor invasion, metastasis, and drug resistance. However, the spatial distribution of hypoxia-related heterogeneity in PDAC remains unclear. Methods: Spatial transcriptomics (STs), a new technique, was used to investigate the ST features of engrafted human PDAC in the ischemic hind limbs of nude mice. Transcriptomes from ST spots in the hypoxic tumor and the control were cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…25,26 Hypoxia, CSCs, and EMT are the main factors in VM formation. 27,28 VM formation in GC may involve a variety of molecules, including Lncrna-pvt1, galectin-1, and HMGA2, inducing VM by regulating EMT-related factors. [29][30][31] TAZ is highly expressed in many tumors and plays a key role in tumor cell proliferation, migration, stemness, and EMT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Hypoxia, CSCs, and EMT are the main factors in VM formation. 27,28 VM formation in GC may involve a variety of molecules, including Lncrna-pvt1, galectin-1, and HMGA2, inducing VM by regulating EMT-related factors. [29][30][31] TAZ is highly expressed in many tumors and plays a key role in tumor cell proliferation, migration, stemness, and EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia, CSCs, and EMT are the main factors in VM formation 27,28 . VM formation in GC may involve a variety of molecules, including Lncrna‐pvt1, galectin‐1, and HMGA2, inducing VM by regulating EMT‐related factors 29–31 .…”
Section: Discussionmentioning
confidence: 99%
“…This study first describes the spatial gene expression changes of ductal adenocarcinoma of the breast induced by a hypoxic microenvironment, and it identifies its potential therapeutic targets, which can provide the foundation for further studies of prognosis and treatment of hypoxic tumors. Spatial heterogeneity of hypoxic tumors and control tissue in breast cancer was studied by Sun et al (2021) . ST results showed that tumor cell subgroups decreased to seven subsets compared to the nine subgroups of the normal control.…”
Section: In Situ Gene Expression Profiling By Spatial Transc...mentioning
confidence: 99%
“…Different subsets exhibit positional features and different gene features. Next, subgroups located at the forefront of invasion exhibited active functions under hypoxic conditions, including cell proliferation, invasion, and stress response, as well as the uneven distribution of hypoxia-related genes across subsets ( Sun et al, 2021 ). These studies suggest that ST is able to dissect the heterogeneity in biopsy that cannot be detected by conventional transcriptome analysis, which may provide more detailed prognostic information.…”
Section: In Situ Gene Expression Profiling By Spatial Transc...mentioning
confidence: 99%
“…In a study involving engrafted human PDAC in ischemic hind limbs of nude mice, gene expression was observed to vary spatially depending on oxygenation of the microenvironment 78 . In the control group (normoxic conditions), the subgroups (SG) identified by spatial transcriptomics had diverse functions, such as enrichment of genes involved in proliferation in SG2, SG3, SG4 and SG11, but under hypoxic condition only SG6 showed properties of proliferation.…”
Section: Spatial Transcriptomics In Cancermentioning
confidence: 99%